Law Enforcement of Criminal Acts of Fraud Through Electronic Media by The Electronic Information Technology Law (UU ITE) in the Jurisdiction of The Karangasem Resort Police - Alit, I Gede; Zuhro Nurindahwati (International Journal of Contemporary Sciences (IJCS), 2024)
Crimes caused by the development and advancement of information technology and telecommunications are criminal acts of fraud through electronic media. Karangasem Resort Police Investigators in law enforcement against criminal acts of fraud through electronic media use a legal basis based on Article 28 paragraph (1) of the ITE Law. There is a conflict of legal norms in law enforcement against the crime of fraud specifically where Article 378 of the Criminal Code carries a penalty of only 4 years while the crime of fraud through electronic media by disseminating invalid or false news to cause losses is regulated in Article 28 paragraph (1) of the ITE Law which carries a penalty of up to 6 years. For this reason, police investigators if there is a criminal act of fraud through electronic media must be able to dig deeper into the criminal act of fraud, whether the article imposed is sufficient to use the Criminal Code or can be conjoined with the ITE Law. The obstacles faced by investigators of the Karangasem Resort Police are motivated by the fact that there are still few law enforcement officers who understand the ins and outs of information technology (internet), limited facilities and infrastructure, and lack of public legal awareness in efforts to overcome criminal acts of information technology